UJI PASIR LIMBAH TAMBANG INTAN CEMPAKA - Haryanti, Ninis Hadi (Lambung Mangkurat University Press, 2015)
ABSTRACT. During diamond mining process, waste is usually found. That diamond mine waste (tailing) that is categorized as gangue mineral is sand and gravel. One of gangue minerals which are in the form of sand during diamond mine in Cempaka Banjarbaru is Zircon sand.Â Until now, that zircon sand has not been utilized optimally. Based on the size measurement of sand grains from diamond mine waste, it is passed the standard of filter size number 4 and related with 4.75 mm filter hole. However the result includes 2.69 Apparent Specific Gravity as well as 1.41 g/cm3 density. That result is categorized into normal aggregate type and lower compared to other sand location (Matraman area). By looking at the morphology and size of sand grains from diamond mine waste, it is gained smaller and tighter particles distribution, equal particle distribution and varied particle size. When looking at the form of sand grains, that diamond mine waste sand is categorized under Sub Angular Grain. Based on EDX spectrum analysis result, it is contained C, O, Al, Si, Ti, Fe, Cu, Zr. Based on 3 different samples of diamond mine waste sand, it is gained average Zr value which is the first Zr sample 1.5, the second Zr sample 0.485, the third Zr sample 0.925. The highest Zr value is in the first sample, which is the sample in sand container box, with average Zr 1.5% composition of Zircon. From the 3 samples of diamond mine waste sand in the different location, it is gained average Zr values which are the first Zr sample 1.5, the second Zr sample 0.485, the third Zr sample 0.925. The highest Zr value is in the first sample, which is the sample in sand container box, with average Zr 1.5% composition of Zircon.Â Keywords : diamond mine waste, Zircon sand